1995
DOI: 10.1090/s0025-5718-1995-1265018-4
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorandom vector generation by the multiple-recursive matrix method

Abstract: Abstract.Pseudorandom vectors are of importance for parallelized simulation methods. In this paper we carry out an in-depth analysis of the multiplerecursive matrix method for the generation of uniform pseudorandom vectors which was introduced in an earlier paper of the author. We study, in particular, the periodicity properties, the lattice structure, and the behavior under the serial test for sequences of pseudorandom vectors generated by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this paper we show that if we vary the -splitting subspace or, in other words, if we pick a ''good'' -splitting subspace, then we can get results that are nearly best possible. This completes a task posed by the author in [10,Section 6]. We remark that a brief announcement (without proofs) of the results of the present paper is contained in [12].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…In this paper we show that if we vary the -splitting subspace or, in other words, if we pick a ''good'' -splitting subspace, then we can get results that are nearly best possible. This completes a task posed by the author in [10,Section 6]. We remark that a brief announcement (without proofs) of the results of the present paper is contained in [12].…”
Section: Introductionsupporting
confidence: 54%
“…with an explicitly given ms-dimensional lattice L. For s Ͼ k there is a figure of merit associated with the points in (15) by [10,Definition 3]. As in Section 2 we write…”
Section: Results For Pseudorandom Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a preliminary version of this paper was prepared, we found that the seemingly new notion of a σ-LFSR can, in fact, be traced back to the work of Niederreiter (1993Niederreiter ( -1996 mainly in the context of pseudorandom number generation. Indeed, in a series of papers [12,13,14,15], Niederreiter has introduced the so called multiple recursive matrix method and the notion of recursive vector sequences. The latter are essentially the same as sequences generated by a σ-LFSR, modulo a natural isomorphism between the field F q m with q m elements and the vector space F m q of dimension m over The question of counting the number of primitive σ-LFSRs of a given order n over F q m is considered in [13, p. 11] under a different guise (cf.…”
Section: Introductionmentioning
confidence: 99%